Genomes of sequence type 121 Listeria monocytogenes strains harbor highly conserved plasmids and prophages - Schmitz-Esser, Stephan; Müller, Anneliese; Stessl, Beatrix; Wagner, Martin (Frontiers in Microbiology, 2015)
The food-borne pathogen Listeria (L.) monocytogenes is often found in food production environments. Thus, controlling the occurrence of L. monocytogenes in food production is a great challenge for food safety. Among a great diversity of L. monocytogenes strains from food production, particularly strains belonging to sequence type (ST)121 are prevalent. The molecular reasons for the abundance of ST121 strains are however currently unknown. We therefore determined the genome sequences of three L. monocytogenes ST121 strains: 6179 and 4423, which persisted for up to 8 years in food production plants in Ireland and Austria, and of the strain 3253 and compared them with available L. monocytogenes ST121 genomes. Our results show that the ST121 genomes are highly similar to each other and show a tremendously high degree of conservation among some of their prophages and particularly among their plasmids. This remarkably high level of conservation among prophages and plasmids suggests that strong selective pressure is acting on them. We thus hypothesize that plasmids and prophages are providing important adaptations for survival in food production environments. In addition, the ST121 genomes share common adaptations which might be related to their persistence in food production environments such as the presence of Tn6188, a transposon responsible for increased tolerance against quaternary ammonium compounds, a yet undescribed insertion harboring recombination hotspot (RHS) repeat proteins, which are most likely involved in competition against other bacteria, and presence of homologs of the L. innocua genes lin0464 and lin0465.